Implementing Scientific Approach in Islamic Education Class - Syabana, Irhas (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
The 2013 curriculum requires that learning be carried out with a scientific approach, ie an approach done as one conducts scientific research. Considering the 2013 curriculum has been established with the Regulation of the Minister of Education and Culture number 65 in 2013, but there are many schools that have not implemented it completely. Therefore, the author wants to know how the implementation of the curriculum with a scientific approach in the subject of SMPN Kayen Kediri. The results showed that there are 5 stages done in learning with a scientific approach, namely observing, asking, collecting information, reasoning and communicate. Although the teacher has been trying to activate students in the acquisition of subject matter, but the changes obtained are not significant. The reason is due to the limitations of teachers in preparing the facilities needed in learning. In addition, because most learners do not have independence in learning.